Using life course charts to assess and compare trajectories of amphetamine type stimulant consumption in different user groups: a cross-sectional study - Addison, Michelle (2020)
Background: Amphetamine-type stimulants (ATS) are the second most commonly used illicit drugs in Europe and globally. However, there is limited understanding of what shapes patterns of ATS use over the life course. The ATTU NE project “Understanding Pathways to Stimulant Use: a mixed methods examination of the individual, social and cultural factors shaping illicit stimulant use across Europe” aims to fill this gap. Here we report initial findings from the life course chart exercise conducted as part of qualitative interviews with ATS users and nonusers. Methods: Two hundred seventy-nine in-depth qualitative interviews were conducted with five ATS user groups (current and former dependent users; current and former frequent users; non-frequent users) and one group of exposed non-ATS users in five European countries (Germany, UK, Poland, Netherlands and Czech Republic). As part of the interviews, we used life course charts to capture key life events and substance use histories. Life events were categorised as either positive, neutral or negative, and associated data were analysed systematically to identify differences between user groups. We applied statistical analysis of variance (ANOVA) and analysis of covariance (ANCOVA) to test for group differences. Results: Out of 3547 life events documented, 1523 life events were categorised as neutral, 1005 life events as positive and 1019 life events as negative. Current and formerly dependent ATS users showed more negative life events for the entire life course after age adjustment. Although some group differences could be attributed to the individuals’ life course prior to first ATS use, most negative life events were associated with periods of ATS usage. A detailed analysis of the specific life domains reveals that dominantly, the social environment was affected by negative life events. Conclusions: For non-dependent, frequent and non-frequent ATS users, negative life events from the period of ATS use do not become obvious in our analysed data. Besides preventing a pathway into ATS dependency, the aim of an intervention should be to reduce the harm by for example drug testing which offers also the opportunity for interventions to prevent developing a substance use dependency. For the group of dependent ATS users, our study suggests holistic, tailored interventions and specialist treatment services are needed, as a single, simple intervention is unlikely to cover all the life domains affected